WTO reform: Issues in special and differential treatment (S&DT) - Anwarul Hoda (Indian Council for Research on International Economic Relations (ICRIER), 2021)
This paper evaluates the special and differential treatment provisions in the WTO Agreement and examines whether there is truth in the averment made by certain developed countries that special and differential treatment (S&DT) provisions have made the WTO framework of rules and disciplines asymmetrical. It comes to the conclusion that for the most part, the S&DT provisions in the WTO Agreement provide only minor to very minor benefits to developing countries and sometimes no benefits at all. The rule of less than full reciprocity in tariff negotiations did no doubt provide meaningful benefits in the past but, in the WTO era, the developed countries have sharply escalated the demand for reciprocity and the value of this provision stands very much diminished. In agriculture, although major benefits are provided to developing countries by way of S&DT, these were more than counterbalanced by the more significant advantages provided to developed countries. The paper also analyses the proposal of developed countries to end the current practice of self-declaration to determine the development status of a Member and to deny the benefit of S&DT to certain categories of advanced developing countries in future negotiations. It points out that when the S&DT was initially introduced in GATT 1947, the main concern was the low standard of living that prevailed among developing countries and argues that any change in the development status of a WTO Member should logically be on the basis of a rise in its standard of living.
Keywords: F13; F53; F55; 330; Special and Differential Treatment; World Trade Organisation